Honey Bees and Environmental Stress: Toxicologic Pathology of a Superorganism. (December 2019) - Berenbaum, May R.; Liao, Ling-Hsiu
As a eusocial species, Apis mellifera, the European honey bee, is effectively a superorganism —a group of genetically related individuals functioning as a collective unit. Because the unit of selection is the colony and not the individual, standard methods for assessing toxicologic pathology can miss colony-level responses to stress. For over a decade, US populations of honeybees have experienced severe annual losses attributed to a variety of environmental stressors varying temporally and geographically; differentiating among those stressors is accordingly a high priority. Social interactions among individuals in this social species, however, mean that the "footprint" of stressors such as pesticides, phytochemicals, pathogens, and parasites may be most discernible in individuals that did not themselves directly encounter the stressor. For example, neurotoxic effects of pesticides on nurse bees may impair their behavioral responses to queen-destined larvae, which may then emerge as adults with altered anatomy or physiology. Similarly, pesticide-induced size alterations in nurse hypopharyngeal glands, which produce royal jelly, the exclusive food of larval and adult queens, may disproportionately affect the queen's (and thus colony) health. Thus, evaluating toxicologic pathology in the honeybee requires a new perspective and development of assays that preserve the social context that ultimately determines colony health.